2015
DOI: 10.1002/cam4.465
|View full text |Cite
|
Sign up to set email alerts
|

Reduced risk of breast cancer associated with recreational physical activity varies by HER2 status

Abstract: Convincing epidemiologic evidence indicates that physical activity is inversely associated with breast cancer risk. Whether this association varies by the tumor protein expression status of the estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), or p53 is unclear. We evaluated the effects of recreational physical activity on risk of invasive breast cancer classified by the four biomarkers, fitting multivariable unconditional logistic regression models to data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
1
11
0
2
Order By: Relevance
“…The presence of chemicals generated by smoking has been detected in mammary gland tissue of both healthy women and breast cancer patients (50)(51)(52). In vitro studies suggest that nicotine (31), benzo(a) pyrene (53), 1-methylanthracene (54), and penanthrene (55) may provoke alterations in epigenetic and transcriptional mechanisms which regulates the expression of genes that are involved in transformation of healthy epithelial cells, proliferation, and metastasis of tumor epithelial cells into the mammary gland (26). There are carcinogens in tobacco smoke such as polycyclic aromatic hydrocarbons (PAH), aromatic amines, and nitrosoamines (20), and these carcinogens can have both estrogenic (56) and antiestrogenic effects (57,58).…”
Section: Smokingmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of chemicals generated by smoking has been detected in mammary gland tissue of both healthy women and breast cancer patients (50)(51)(52). In vitro studies suggest that nicotine (31), benzo(a) pyrene (53), 1-methylanthracene (54), and penanthrene (55) may provoke alterations in epigenetic and transcriptional mechanisms which regulates the expression of genes that are involved in transformation of healthy epithelial cells, proliferation, and metastasis of tumor epithelial cells into the mammary gland (26). There are carcinogens in tobacco smoke such as polycyclic aromatic hydrocarbons (PAH), aromatic amines, and nitrosoamines (20), and these carcinogens can have both estrogenic (56) and antiestrogenic effects (57,58).…”
Section: Smokingmentioning
confidence: 99%
“…The association between physical activity and breast cancer subtypes have been investigated in several studies (26)(27)(28)(29)(30)(31)(32)(35)(36)(37). Some of these studies had information on ER only, ER and PR (27,(30)(31)(32)37), and others had information on ER, PR, and HER2 (26,28,29,35,36). Of all these studies, two of them had fewer than 700 cases (29,35) and six studies included from 1,921 to 5,882 cases (26-28, 31, 32, 36).…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies reported statistically significant association only among women with ER+ or ER+/PR+ breast cancer [43][44][45][46][47], whereas three studies found risk reduction limited to women with ER-or ER-/PR-breast cancer [3,48,50]. Only three studies to date have investigated the association between recreational physical activity and TNBC [4][5][6]. The Women's Health Initiative Cohort Study reported that risks of both TNBC and ER+ breast cancer were inversely associated with recreational physical activity among postmenopausal women [4].…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to evaluate risk of triple negative breast cancer (TNBC, ER-/PR-/HER2-) in the earlier publication because HER2 data were not available for cases diagnosed before 1999. To our knowledge, only the Women's Health Initiative Cohort Study [4] and two case-control studies [5,6] have investigated the association between recreational physical activity and TNBC risk.…”
Section: Introductionmentioning
confidence: 99%